Description of Physical Activity and the Incident of Coronary Heart Disease - Susanti, Nofi; Lea, Salshabilla April; Mutiara, Yusnidar Sari; Moely, Cut Mulyana; Marpaung, Mimbi Gusrera (PROMOTOR, 2024)
Coronary heart disease (CHD) is one of the most common cardiovascular diseases and causes the highest number of deaths globally. This study aims to describe the relationship between physical activity and the incidence of CHD. The research method used is a literature review, where data is collected from various related studies. The results showed that physical activity was significantly related to the incidence of CHD. CHD patients tend to do light physical activity because heavy activity can cause pain and discomfort. This study emphasizes the importance of regular physical activity in preventing and managing CHD. In conclusion, there is a significant relationship between the level of physical activity and the incidence of CHD, and regular physical activity can improve the quality of life of CHD patients.